2002
DOI: 10.1212/wnl.58.10.1494
|View full text |Cite
|
Sign up to set email alerts
|

Molecular findings in symptomatic and pre-symptomatic Alexander disease patients

Abstract: In symptomatic and asymptomatic patients with a predominantly frontal leukoencephalopathy by MRI, GFAP gene mutation analysis should be included in the initial diagnostic evaluation process for Alexander disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 21 publications
4
71
0
Order By: Relevance
“…Recently, mutations in the glial fibrillary acidic protein (GFAP) gene were identified in AD patients [3][4][5]. This has facilitated the genetic diagnosis of mild AD patients, and the discovery of different clinical manifestations of AD [4][5][6][7][8][9]. However, genotype-phenotype correlations have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mutations in the glial fibrillary acidic protein (GFAP) gene were identified in AD patients [3][4][5]. This has facilitated the genetic diagnosis of mild AD patients, and the discovery of different clinical manifestations of AD [4][5][6][7][8][9]. However, genotype-phenotype correlations have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, Alexander disease is classified into three subtypes: infantile, juvenile, and adult forms, based on the age at disease onset. Recently, GFAP mutations have been reported in various forms of Alexander disease Aoki et al 2001;Rodriguez et al 2001;Shiroma et al 2001;Gorospe et al 2002;Li et al 2002;Meins et al 2002;Namekawa et al 2002;Probst et al 2003;Sawaishi et al 2002;Shiihara et al 2002;Shiroma et al 2003;Suzuki et al 2004) and we have identified juvenile and adult forms of Alexander disease with three different GFAP mutations: V87G (Okamoto et al 2002), R88C (Nobuhara et al 2004) and R416W (Kinoshita et al 2003). To date, there had been few reports investigating the properties of mutant GFAP (Li et al 2005;Hsiao et al 2005;Perng et al 2006).…”
Section: Introductionmentioning
confidence: 84%
“…Gorospe et al, reported 12 genetically confirmed cases of AD including seven with infantile onset. All had megalencephaly at presentation [8]. Li et al, studied 26 infantile AD out of 44 patients with AD and found macrocephaly in 62 % cases.…”
Section: Discussionmentioning
confidence: 99%